Urgensi Fotografi dalam Aktivitas Dakwah Islam - Fachry Abda El Rahman; Nia Kurniati Syam (Bandung Conference Series: Islamic Broadcast Communication, 2022)
Abstract. Da'wah activities are activities that are carried out consciously for the realization of people who have strong religious characteristics and good morals and hold fast to the Qur'an and As-Sunnah. From the research that the author did about the urgency of photography in Islamic da'wah activities. The objectives and benefits of this research are as follows: 1. To find out the role of photography in Islamic da'wah activities. 2. To find out the importance of photography in Islamic da'wah activities. 3. To find out the impact of photography in Islamic da'wah activities. The research method used is descriptive qualitative analysis method, data collection techniques: interviews, documentation, and literature study. The results showed that the urgency of photography in Islamic da'wah activities has concluded that photography in Islamic da'wah activities is very important, from its benefits and impacts on Islamic da'wah activities. So the conclusion is that 1) the role of photography in Islamic da'wah activities is quite a lot. 2) the importance of photography in Islamic da'wah activities is very important for Islamic da'wah. 3) the impact of photography on Islamic da'wah activities is quite a lot and needs to be developed again so that photography becomes a medium for developing Islamic da'wah. Abstrak. Aktivitas Dakwah merupakan kegiatan yang dilakukan secara sadar demi terwujudnya umat yang mempunya sifat keagamaan yang kuat dan akhlak yang baik serta berpegang teguh kepada Al-Qur’an dan As-Sunnah. Dari penelitian yang penulis lakukan tentang urgensi fotografi dalam aktivitas dakwah Islam. Tujuan dan Manfaat penelitian ini sebagai berikut: 1. Untuk mengetahui peran fotografi dalam aktivitas dakwah Islam. 2. Untuk mengetahui pentingnya fotografi dalam aktivitas dakwah Islam. 3. Untuk mengetahui dampak fotografi dalam aktivitas dakwah Islam. Metode Penelitian yang digunakan adalah Metode Kualitatif Deskriptif Analisis, teknik pengumpulan data: wawancara, dokumentasi, dan studi kepustakaan. Hasil penelitian diperoleh bahwa urgensi fotografi dalam aktivitas dakwah Islam telah disimpulkan bahwa fotografi dalam aktivitas dakwah Islam sangat penting, dari manfaatnya dan dampaknya terhadap aktivitas dakwah Islam. Jadi kesimpulannya adalah bahwa 1) peran fotografi dalam aktivitas dakwah Islam cukup banyak. 2) pentingnya fotografi dalam aktivitas dakwah Islam sangat penting terhadap dakwah Islam. 3) dampak fotografi terhadap aktivitas dakwah Islam cukup banyak dan perlu dikembangkan lagi agar fotografi menjadi media untuk mengembangkan dakwah Islam.